High intensity social conflict in the Swiss albino mouse induces analgesia modulated by 5-HT1A receptors - DeSouza, A. C.; deSouza, RLN; Pela, I. R.; Graeff, F. G. (Elsevier B.V., 1997)
Social conflict between mice produces analgesia in the attacked mouse. Both the magnitude and type (opioid or nonopioid) of this analgesia have been related to attack intensity and strain of mouse. In the present study low intensity social conflict (7 bites) did not produce analgesia, whereas high intensity - 30 and 60 bites interactions produced, respectively, short-lasting (5 min) and very short-lasting (1 min) analgesia in Swiss albino mice, when compared with nonaggressive interaction (0 bite). The 30 bites aggressive interaction induced analgesia (AIIA) was not affected by IP injection of either naloxone (5.0 and 7.5 mg/kg) or diazepam (0.5, 1.0, 2.0 and 4.0 mg/kg). However, this attack-induced analgesia was reduced after IP administration of the 5-HT1A agonists, gepirone (0.3 and 3.0 mg/kg) and BAY R 1531 (0.01 mg/kg). These results indicate that the analgesia induced by 30 bites social conflict in Swiss albino mice does not involve opioid and GABA-benzodiazepine (GABA-BZD) mechanisms. In addition, they suggest that high-intensity social conflict activates serotonergic pain modulatory systems that act through 5-HT1A receptors. Copyright (C) 1997 Elsevier B.V.
Keywords: social conflict; analgesia; naloxone; diazepam; 5-HT1A agonists; Swiss albino mice